2020
DOI: 10.1371/journal.pone.0223631
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality as a tool for environmental conservation and fundraising

Abstract: Anecdotal evidence from philanthropic fundraisers shows that virtual reality (VR) technology increases empathy and can influence people toward pro-environmental behavior. Non-profit organizations are increasingly marketing their causes using virtual reality and they report increased donations when VR technology is employed. In VR, users are immersed in situations intended to feel more like the real world through technology, such as 360˚video viewed through 3D headsets that block out visual and auditory distrac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 38 publications
(31 reference statements)
2
39
0
Order By: Relevance
“…In order to design the bid structure for nightly price premiums for the survey, we drew on previous revealed preference donation studies conducted by the authors in Gili Trawangan [ 23 , 62 ] and knowledge of other voluntary donations for environmental conservation solicited on the island. In addition, following the procedure described by Champ et al, [ 55 ], we conducted a pilot test with 50 randomly sampled tourists employing an open-ended question wherein participants were provided with the following scenario and question:…”
Section: 0 Methodologymentioning
confidence: 99%
“…In order to design the bid structure for nightly price premiums for the survey, we drew on previous revealed preference donation studies conducted by the authors in Gili Trawangan [ 23 , 62 ] and knowledge of other voluntary donations for environmental conservation solicited on the island. In addition, following the procedure described by Champ et al, [ 55 ], we conducted a pilot test with 50 randomly sampled tourists employing an open-ended question wherein participants were provided with the following scenario and question:…”
Section: 0 Methodologymentioning
confidence: 99%
“…For example, in a virtual reality-based intervention, it was tested whether gain or loss framing was more influential in provoking respondents to be willing to donate money and time for biodiversity conservation organizations (Nelson et al, 2020). The authors found that the negatively framed audio together with 360°virtual reality video resulted in more money donated, but only in the context of tourists that were immediately impacted by the health of the natural resource-which in this case happened to be coral reefs.…”
Section: Framing Effectsmentioning
confidence: 99%
“…The authors found that the negatively framed audio together with 360°virtual reality video resulted in more money donated, but only in the context of tourists that were immediately impacted by the health of the natural resource-which in this case happened to be coral reefs. Respondents' behavioral attitudes were not a significant indicator for their behavior (Nelson et al, 2020). Ahn et al (2015) conducted a virtual experiment with a visual framing (instead of semantic framing) in which subjects were exposed to either cutting (negative) or planting (positive) a tree in an animation.…”
Section: Framing Effectsmentioning
confidence: 99%
See 2 more Smart Citations